MEMPERINGATI TIGA ABAD LINNAEUS - Rani Asmarayani (Research Center for Biology-Indonesian Institute of Sciences, 2007)
One of the scientists,whose name is still inherently kept in scientists' mind nowadays, is Carolus Linnaeus. He is known as the Father of Taxonomy who has laid down the principles of taxonomy. His contributions to this discipline were inevitably giving new paradigm. Commemorating his such great and invaluable contributions on science today after 300 years, a reflection for tracking his journey, history of life and contributions to science - especially in Indonesia, is presented in this paper.